Laporan Kasus: Hematokolpos et Hematometra e.c Septum Vagina Transversal - Km Allan Wahyu Permana; Ghaaliya dyah adheline; Nurul Islamy; Marzuqi Sayuti (Medula, 2021)
Transverse vaginal septum is rare mullerian duct anomaly, the incidence was report around 1 : 70.000 in every birth, transverse vaginal septum occures due to failure of canalization of vaginal plate in junction point of urogenital sinus and mullerian duct, usually with obstruction symtoms during menstruation. Classification of mullerian duct anomaly divide into 7 class, hypoplasia or agenesis, unicomuate, didelphys, bicornuate, septate, arcuate, and diethulstillbestrol related anomaly. Diagnosis of transverse vaginal septum was made on basis of medical sign and symtoms, physical examination, and ultrasound examination, CT Scan, or MRI. Treatment of septum vaginal transversal is surgical resection of septum vagina. This study is a case report at Abdul Moeloek Hospital in Bandarlampung. It has been reported the case of a female patient aged 10 years, patient compained of pain in lower abdomen since september, pain felt every month, patient has not had menarche. Physical examination shows swelling in suprapubic with no pain in palpation. Gynecology examination with sonde show length of vagina is 4 cm.  In rectal touche there was impression of mass in anterior to the rectum. On ultasound examination show hematocolpos and hematometra, CT scan examination show the impression of hematocolpos and hydrosalping bilateral. Patient was diagnosed with Hematocolpos et hematometra e.c. septum transversal